The Epistemological Framework of Indonesian Feminist Thought: An Analytical Study of Faqihuddin Abdul Kodir’s Qirā’ah Mubādalah Method in Qur’anic Interpretation - Rohman, Baeti; Amin, Arwani (Institut Agama Islam Negeri (IAIN) Keiri, 2025)
This study examines the epistemological structure of Qirā’ah Mubādalah, an interpretive method formulated by Faqihuddin Abdul Kodir that has gained traction over the past five years, including its adoption within the KUPI Fatwa Methodology. Using qualitative library research—drawing on Faqih’s Qirā’ah Mubādalah as the primary source and theses, dissertations, and scholarly articles as secondary materials—the study maps foundational references, operational logic, and epistemic positioning that undergird its application. Findings indicate that Mubādalah rests on the apparatus of istinbāṭ al-ḥukm within a thematic fiqh framework, supported by maqāṣid (justice, public welfare) and a tawḥīdic ethical horizon (justice, wisdom, compassion, welfare), which together furnish transformative normative force and a three-step workflow. Yet the analysis also exposes methodological vulnerabilities: a blurred boundary between fiqh and tafsīr, the risk of “values preceding the text,” and thematic bias because explicit applications cluster around gender. In response, the article proposes a reordered operative sequence—first securing linguistic–historical meaning, then activating the ethical horizon for application—alongside deliberate cross-theme testing (ritual worship, transactions, environmental ethics, governance, criminal justice) and a clear epistemic positioning (fiqh analytic tool, tafsīr method, feminist hermeneutics, or feminist daʿwah praxis). The study’s contribution lies in clarifying Mubādalah’s epistemic frame and operational protocol, thereby strengthening methodological coherence, scholarly accountability, and social impact.